Fair DSL-LTE Dynamic Spectrum Design Based-Utility Functions on Multiple Quality of Service Network - Puspita, Fitri Maya; Rahmadia, Putri; Yuliza, Evi; Indrawati, Indrawati; Sitepu, Robinson; Octarina, Sisca; Yunita, Yunita (Journal of Applied Science, Engineering, Technology, and Education, 2023)
The purpose of this research is to formulate a C-RAN(Cloud-Radio Access Network) model based on a fair network combined with an isoelastic utility function and a modified cobb-douglas utility function and then optimize the consumer problem on bandwidth consumption by dividing the financing scheme into three, namely flat-fee, usage-based, and two-part tariff. This research uses traffic data containing inbound and outbound data with two split time which are in off-peak and on-peak hours. The data is obtained through one of the local server in Palembang. Previous research informed that the C-RAN model get optimal benefit if Internet Service Provider (ISP) applies it. The improvement of the model is to be conducted using two utility function to seek for improved solutions. The new proposed model has best solution that has been improved using an isoelastic utility function of flat-fee financing type with an objective value obtained of 1.83333 with 17 iterations. It can be concluded that new designed model can achieve better results rather than old version involving C-RAN model